2021
DOI: 10.1002/cam4.4398
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA: A promising new star for the diagnosis and treatment of colorectal cancer

Abstract: Colorectal cancer (CRC) is one of the most common malignant tumors of the digestive tract, and morbidity and mortality rank third and second in malignant tumors. [1][2][3] Currently, early screening for CRC can effectively improve the survival rate of patients with CRC, but approximately 25% of CRC patients develop metastatic disease from an early stage. [4][5][6] Therefore, a promising field of antimetastatic therapy lies in the targeted inhibition of cancer cells with high metastatic potential from the prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 125 publications
1
25
0
Order By: Relevance
“…CircRNAs were mainly formed during the processing of RNA polymerase II performing transcriptional functions according to the central dogma ( 50 ). Due to the uncertainty of the gene transcription process, the biosynthesis of circRNAs also had various mechanisms including intron pairing mediated circularization, RNA binding protein mediated circularization, alternative splicing mediated circularization (lariat-driven) and canonical linear splicing mediated circularization (intronic lariat-driven) ( 51 ). According to the splicing method and the corresponding product structure characteristics at the same time, circRNAs could be divided into three types including: exonic circRNAs (ecRNAs), exon-intron circRNAs (EIciRNAs) and intron circRNAs (ciRNAs).…”
Section: The Biogenesis and Classification Of Circrnasmentioning
confidence: 99%
“…CircRNAs were mainly formed during the processing of RNA polymerase II performing transcriptional functions according to the central dogma ( 50 ). Due to the uncertainty of the gene transcription process, the biosynthesis of circRNAs also had various mechanisms including intron pairing mediated circularization, RNA binding protein mediated circularization, alternative splicing mediated circularization (lariat-driven) and canonical linear splicing mediated circularization (intronic lariat-driven) ( 51 ). According to the splicing method and the corresponding product structure characteristics at the same time, circRNAs could be divided into three types including: exonic circRNAs (ecRNAs), exon-intron circRNAs (EIciRNAs) and intron circRNAs (ciRNAs).…”
Section: The Biogenesis and Classification Of Circrnasmentioning
confidence: 99%
“…Overexpression of H19 promotes malignant behavior and induces apoptosis. H19 promotes the expression of the EMT-related marker miR-675 and inhibits p53 expression (Shunhao Zhang et al, 2021). Hcp5 can upregulate EZH2 expression by competitively binding to miR-138-5p, promoting autophagy and suppressing apoptosis by regulating the STAT3/ VEGFR2 pathway, leading to malignant progression of CSCC (Zou et al, 2021).…”
Section: Figurementioning
confidence: 99%
“…Throughout the last decade of research, we have identified a series of circRNAs [ 142 ] as biomarkers of oncogenic/tumor-suppressive genes that exert anti-colorectal-cancer functions. Although the regulation of these functional molecules of circRNAs has gradually entered public view, the research on circRNAs has just begun.…”
Section: Curcumin and Colorectal Cancer Therapy Based On Non-coding R...mentioning
confidence: 99%